'A universal, uniform humanity': the German newspaper Der Kosmopolit and entangled nation-building in nineteenth-century Australia. Issue 1 (2nd January 2018) - Mischke, Dennis
ABSTRACT: The focus in this article, through a reading of the German-Australian newspaper Der Kosmopolit, is on the legacies of entangled imperial identities in the period of the nineteenth-century German Enlightenment. Attention is drawn to members of the liberal nationalist generation of 1848 who emigrated to the Australian colonies and became involved in intellectual activities there. The idea of entanglement is applied to the philosophical orientation of the German-language newspaper that this group formed, Der Kosmopolit, which was published between 1856 and 1957. Against simplistic notions that would view cosmopolitanism as the opposite of nationalism, it is argued that individuals like Gustav Droege and Carl Muecke deployed an entangled 'cosmo-nationalism' in ways that both advanced German nationalism and facilitated their own engagement with and investment in Australian colonial society.